SOFT TISSUES GUNSHOT DEFECTS ULTRASOUND INVESTIGATION USE IN RECONSTRUCTIVE-RESTORATIVE SURGERY - Khomenko, I.P.; Tertyshnyi, S.V.; Vastyanov, R.S.; Talalayev, K.O. (World of Medicine and Biology, 2021)
During the Joint Forces operation in Eastern Ukraine the provision of surgical care modern technology treatment and rehabilitation of wounded with soft tissues gunshot defects is one of the governmental priorities. The current state of this problem characterizes by soft tissue gunshot wounds incidence increase. 34 patients with soft tissues gunshot wounds among all admitted for medical care were selected and were treated using differentiated surgical tactics using blood vessels ultrasound duplex examination. We did not register any episode of complications in patients during intra- and postoperative period of treatment. Our data revealed vessels ultrasound duplex examination high reproducibility, easiness of use during intra- and postoperative care and effectiveness. The introduction of the original differentiated surgical tactics to wounded with a multimodal approach to the soft tissues gunshot defects reconstruction helped to reduce traumatic illness complications, number of postoperative purulent-destructive and thromboembolic complications.
Keywords: ultrasound; diagnostic; treatment; gunshot defects; reconstruction; surgery; new concept